Composite current collector and preparation method thereof

By forming an embedded structure in the composite fluid and depositing a metal film layer, the problem of insufficient bonding force between the base film layer of the polymer material and the metal layer is solved, the mechanical strength and service life of the composite fluid are improved, and the electrical performance is enhanced.

CN119133464APending Publication Date: 2024-12-13SHENZHEN XINSAISI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411272721.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The bonding force between the base film layer of the polymer material and the metal layer in the existing composite fluid collecting fluid is insufficient, which affects the electrical performance and service life of the composite fluid collecting fluid.

Method used

By forming an embedded structure on the polymer powder and heating it to weld it, increasing the specific surface area of ​​the film material and the contact area of ​​the metal film layer, the metal film layer is formed by a deposition process to improve the composite strength between the film material and the metal film layer.

Benefits of technology

It significantly improves the mechanical strength and service life of the composite fluid collection, increases the adhesion strength between the metal film layer and the film material, and improves the electrical performance and charge bearing capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133464A_ABST
    Figure CN119133464A_ABST
Patent Text Reader

Abstract

The invention relates to a composite current collector and a preparation method thereof. The preparation method comprises the following steps: laying polymer powder on a preset workpiece; heating the polymer powder so that the polymer powder is welded to form a membrane material; and forming a metal film layer on the film material through a deposition process. Through the technology of forming the embedded structure on the film material and depositing the metal film layer, the metal film layer and the film material can be stably compounded, the mechanical strength of the composite current collector is well improved, and the service life of the composite current collector is well prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collectors, and in particular to a composite current collector and a preparation method thereof. Background Art

[0002] A current collector refers to a structure or part that collects electric current and is mainly used in the battery industry. In addition to current collectors made of pure copper foil and pure aluminum foil, composite current collectors have also been developed. Composite current collectors generally have a three-layer structure, with a polymer layer in the middle layer and metal layers deposited on both sides of the polymer layer. However, the bonding force between the polymer material base film layer and the metal layer of the composite current collector prepared in existing work is insufficient, which affects the electrical properties and service life of the composite current collector. Summary of the invention

[0003] Based on this, it is necessary to provide a composite current collector and a preparation method thereof.

[0004] In a first aspect, a method for preparing a composite current collector is provided, comprising the following steps: Laying polymer powder on the preset workpiece; Heating the polymer powder so that the polymer powder is melted to form a film material; A metal film layer is formed on the film material through a deposition process.

[0005] The preparation method of the composite current collector is to lay the polymer powder on the preset workpiece and heat it, so that the polymer powder is welded, and the polymer powder at the edge forms an uneven embedded structure in microscopic morphology when it is welded. On the one hand, in the deposition stage, the embedded structure increases the specific surface area of ​​the film material, provides more reaction sites, is conducive to the initial adsorption of metal atoms by the film material, and promotes the uniform formation of the metal film layer; on the other hand, in the finished product stage, the embedded structure increases the contact area between the film material and the metal film layer, improves the mechanical interlocking effect between the film material and the metal film layer, and thus improves the composite strength between the film material and the metal film layer.

[0006] By forming an embedded structure in the membrane material and depositing a metal film layer, the metal film layer and the membrane material can be stably composited, thereby improving the mechanical strength and service life of the composite current collector.

[0007] In one of the embodiments, the polymer powder is spread on the preset workpiece, so that the overall surface is smoother when the film material is subsequently formed. In one of the embodiments, the polymer powder is placed on the preset workpiece, and the preset workpiece is vibrated so that the polymer powder gradually spreads out as the preset workpiece vibrates, and is laid flat on the surface of the preset workpiece. In one of the embodiments, the polymer powder is placed on the preset workpiece, and a rod-shaped object is driven to be placed above the preset workpiece and scraped at a preset distance to scrape off the polymer powder that reaches the height of the rod-shaped object, and the polymer powder below the rod-shaped object is retained above the preset workpiece. In one of the embodiments, the feeding mechanism translates along the surface of the preset workpiece at a preset speed, and the polymer powder is delivered at a preset rate to spread a preset amount of polymer powder on the surface of the preset workpiece. The above embodiments can be implemented separately or in combination to make the polymer powder spread on the preset workpiece as much as possible.

[0008] In one embodiment, the polymer powder includes at least one of PE (polyethylene), PP (polypropylene), PET (polyethylene terephthalate), and PI (polyimide). These polymer materials can be welded to form a film material. In one embodiment, the D50 particle size of the polymer powder is 2~10μm. Within this range, the polymer material is easy to form an embedded structure of appropriate size. When the size of the embedded structure is too large, it is easy to cause the metal film layer to become uneven as the shape of the embedded structure fluctuates. When the size of the embedded structure is too small, the metal atoms cannot be effectively embedded between the polymer powders, making it difficult to improve the composite strength of the metal film layer and the film material.

[0009] In one embodiment, after the step of heating the polymer powder so that the polymer powder is welded to form a film material, the step further includes: The film material is separated from the preset workpiece. In the present embodiment, the film material is separated from the preset workpiece, so that the complete film material is removed, so that both sides of the film material are exposed, and then the metal film layer can be deposited on both sides of the film material at the same time. Specifically, after the film material is separated from the preset workpiece, it specifically includes: forming a metal film layer on both sides of the film material through a deposition process, so that the metal film layer is deposited on both sides of the film material to form a composite current collector with a metal film layer on both sides. When the electrode is subsequently prepared, active materials can be set on the surfaces of the two metal film layers. Specifically, the metal film layer has two large surfaces arranged opposite to each other and a side surface located between the two large surfaces. After the film material is separated from the preset workpiece, a metal film layer is formed on the two large surfaces and the side surface of the film material through a deposition process. The uniformly formed metal film layer has a higher continuity, so that the overall coherence of the metal film layer is stronger, and the interface fracture is avoided, so that the metal film layer has better electrical properties.

[0010] In one embodiment, the metal film layer is a copper film layer or an aluminum film layer. Specifically, the metal film layer is deposited from copper or aluminum. The copper film layer and the aluminum film layer are commonly used current collector materials, and are also suitable for the composite current collector material in the present application, and can serve as a conductor for electron transmission.

[0011] In one of the embodiments, the step of separating the film material from the preset workpiece further includes: calendering and / or stretching the film material. In this embodiment, the calendering or stretching operation can more easily make the embedded structure be processed into the required pore size, which is conducive to the embedding of metal atoms, and the film material is processed into the required thickness, which is conducive to controlling the thickness of the film material and then controlling the overall thickness of the composite current collector. In one of the embodiments, the film material is calendered separately. In one of the embodiments, the film material is stretched separately. In one of the embodiments, the film material is calendered and stretched.

[0012] In one embodiment, the preset workpiece includes a release material, so that the film material can be easily separated from the preset workpiece on a side close to the preset workpiece, thereby facilitating other processing on the surface, such as laminating a metal foil layer or depositing a metal film layer on the surface.

[0013] In one embodiment, the release material includes a fluorocarbon material, which can provide a flat surface, is easy for polymer powder to be welded, and has a low surface energy, which can better separate the film material from the fluorocarbon material.

[0014] In one embodiment, the preset workpiece includes a metal foil layer. In this embodiment, the polymer powder is directly welded on the metal foil layer, so that the polymer powder and the metal foil layer are stably combined, and the metal foil layer can be directly used as a conductor of the composite current collector without the need for subsequent separation, and during the welding process, the polymer powder can fully wet the metal foil layer when it melts and then solidifies, so that the film material and the metal foil layer are better composited. After the film material and the metal foil layer are combined, a metal film layer is formed on the film material through a deposition process, and the metal film layer and the metal foil layer are correspondingly arranged on the two surfaces of the film material, thereby forming a composite current collector.

[0015] In one embodiment, the deposition process includes at least one of magnetron sputtering, vacuum evaporation plating, water electroplating and chemical plating. These deposition processes can deposit a metal film layer on the film material, thereby achieving a stable composite of the metal film layer and the film material.

[0016] In one embodiment, the thickness of the metal film layer is 0.5~2μm. A metal film layer that is too thin has weak conductivity and cannot meet the conductivity requirements of the composite current collector. A metal film layer that is too thin is prone to discontinuities, which can easily lead to cracks. A metal film layer that is too thick will cause the metal atoms on the surface to be unable to generate sufficient bonding force with the metal atoms or film materials in the inner layer, causing the metal atoms on the surface to easily fall off and easily increase the weight of the composite current collector, making the battery capacity smaller at the same weight, and also increasing the risk of the metal film layer piercing the diaphragm.

[0017] In one embodiment, the thickness of the film material is 2-8 μm. A film material that is too thin cannot have sufficient mechanical properties, making the film material prone to the risk of fracture, while a film material that is too thick will increase the volume of the composite current collector, resulting in more space required to arrange the current collector, reducing the energy density of the battery.

[0018] In one embodiment, the surface roughness of the film material is 0.012~0.1μm. When the surface roughness is too small, the depth of the embedded structure is too shallow, and the surface of the film material is too smooth to provide sufficient mechanical interlocking effect, which will lead to insufficient bonding strength between the metal film layer and the film material, and lack of sufficient reaction sites to promote the initial adsorption of metal atoms. When the surface roughness is too large, the embedded structure is too deep, which is easy to increase the risk of the film material itself breaking in the thickness direction, and will cause uneven deposition or fracture of the metal film layer, and easily increase the resistance of the composite current collector, affecting the conductive properties of the current collector.

[0019] In one of the embodiments, an embedded structure is formed when the surface of the film material is welded, and the pore size of the embedded structure is 0.2~0.8μm. It is not easy for metal atoms to form inside the embedded structure, and the bonding strength between the metal film layer and the film material is insufficient. When the pore size is too large, it is easy to cause cracks to form on the surface of the film material. These cracks are easy to cause partial peeling of the film material, and drive the metal film layer to peel together, reducing the service life. In one of the embodiments, the D90 pore size of the embedded structure is 0.2~0.8μm, which makes the pore size more uniform, and thus makes the metal film layer more uniform.

[0020] In one embodiment, before the step of forming the metal film layer on the film material by a deposition process, the step further includes: introducing at least one active group of hydroxyl, carbonyl and amino groups on the surface of the film material by a modification process. Specifically, after the active groups such as hydroxyl, carbonyl and amino groups are introduced on the surface of the film material, these active groups can interact better with metal atoms, thereby making the composite strength of the metal film layer and the film material higher.

[0021] In a second aspect, a composite current collector is provided, which is prepared by any of the above-mentioned methods for preparing the composite current collector.

[0022] Since the surface of the membrane material is composed of a large amount of polymer powder, there are pits and gaps on the surface of the membrane material, that is, between adjacent polymer powders. During the formation of the metal film layer, metal atoms can be embedded in these pits and gaps, so the membrane material can greatly improve the adhesion strength with the metal film material.

[0023] The film material obtained in the present application has a larger specific surface area than conventional film materials, and when the thickness of the metal film layer is smaller than the size of the polymer powder, the surface area of ​​the obtained metal film layer is also larger than the area of ​​the conventional composite current collector. Under the same size, the composite current collector of the present application can carry more charges.

[0024] By adjusting the size of the polymer powder, membrane materials with different pore sizes can be easily obtained, and the charge carrying capacity can be more easily adjusted to suit batteries of different models and requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of a process for preparing a composite current collector according to an embodiment; Figure 2 A partially enlarged schematic diagram of a composite current collector and its surface in one embodiment; Figure 3 A schematic diagram of the structure of a composite current collector according to another embodiment; Figure 4 A partial enlarged schematic diagram of the surface of a membrane material of an embodiment; Figure 5 Schematic diagram of the microstructure of the membrane material of Example 1. DETAILED DESCRIPTION

[0026] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0032] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0033] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0034] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.

[0035] In one embodiment, a method for preparing a composite current collector is provided, comprising the following steps: S1, laying polymer powder on a preset workpiece.

[0036] In this step, the polymer powder is evenly spread on the preset workpiece, preferably scraped flat with a scraper, and detected to be free of holes or convex humps, so as to make the film material as flat as possible. The preset workpiece can be a release material or a metal foil layer, wherein the surface of the preset workpiece is flat to evenly support the polymer powder, so as to facilitate the overall surface flatness of the film material.

[0037] S2, heating the polymer powder so that the polymer powder is melted to form a film material.

[0038] In this step, the melting point of the polymer powder is lower than the melting point of the preset workpiece, and the polymer powder can be heated by laser heating, oven or heating plate heating, so that the polymer powder is welded to the surface of the preset workpiece to form a film material. In some embodiments, the polymer material is heated by laser heating, so that all particles of the polymer powder can be evenly heated and welded to form a film material more quickly. Since this heating method has a high heating efficiency, it is more suitable for laying the polymer powder on the metal foil layer and welding it. In some embodiments, the preset workpiece laid with the polymer powder is placed in an oven, and the polymer powder is heated by the oven so that the polymer powder is welded to form a film material. This situation makes the melting speed of the polymer powder slower, but it is suitable for the situation where the polymer powder is welded on the fluorocarbon material or the metal foil layer. In some embodiments, a release material, such as a fluorocarbon material, is coated on one side of the heating plate, and a polymer powder is laid on the release material. The heating is heated on the other side of the heating plate by means of a heating wire, and the heat is evenly conducted to the polymer powder through the heating plate to heat the polymer powder and fuse the polymer powder to form a film material. Since the release material is easy to set on the heating plate, this method is more conducive to preparing a film material on the fluorocarbon material. At the same time, the heating plate can also be set to two, and the two heating plates are pressed from both sides of the film material to better adjust the thickness and flatness of the film material.

[0039] S3, forming a metal film layer on the film material through a deposition process.

[0040] In this step, the deposition process can adopt existing processes, such as one or more of magnetron sputtering, vacuum evaporation plating, water electroplating and chemical plating. During deposition, metal atoms gradually diffuse and adhere to the surface of the film material, so that these metal atoms can be more easily embedded in the embedded structure of the film material, thereby improving the mechanical interlocking effect between the metal film layer and the film material and improving the composite strength.

[0041] The composite current collector prepared by the above preparation method is prepared by laying polymer powder on a preset workpiece and heating it, so that the polymer powder is welded, and the polymer powder at the edge forms an uneven embedded structure in microscopic morphology when it is welded. On the one hand, in the deposition stage, the embedded structure increases the specific surface area of ​​the film material, provides more reaction sites, is conducive to the initial adsorption of metal atoms by the film material, and promotes the uniform formation of the metal film layer; on the other hand, in the finished product stage, the embedded structure increases the contact area between the film material and the metal film layer, improves the mechanical interlocking effect between the film material and the metal film layer, and thus improves the composite strength between the film material and the metal film layer.

[0042] By forming an embedded structure in the membrane material and depositing a metal film layer, the metal film layer and the membrane material can be stably composited, thereby improving the mechanical strength and service life of the composite current collector.

[0043] In one embodiment, the predetermined workpiece includes a release material, and after the film material is formed, the film material is separated from the predetermined workpiece, and a metal film layer is formed on both sides of the film material through a deposition process. Figure 2 The composite current collector shown includes a film material 100 and metal film layers 200 on opposite sides of the film material. According to local magnification, an embedded structure 110 is formed on the surface of the film material 100 to increase the composite strength of the film material 100 and the metal film layer 200.

[0044] In one embodiment, the preset workpiece includes a metal foil layer, which is a prefabricated metal foil. The polymer powder is laid on the metal foil, and one side of the film material is composited with the metal foil during the welding process, and a metal film layer is subsequently formed on the other side of the film material through a deposition process. Figure 3 As shown, the composite current collector includes a film material 100, a metal foil layer 300 and a metal film layer 200, wherein the metal foil layer 300 and the metal film layer 200 are respectively arranged on opposite sides of the film material 100, and one side of the film material 100 is welded on the metal foil layer 300, thereby increasing the composite strength of the film material 100 and the metal foil layer 300, and the embedded structure on the other side of the film material 100 increases the composite strength of the metal film layer 200 and the film material 100.

[0045] In one embodiment, before the step of forming a metal film layer on the film material by a deposition process, the step further includes: introducing at least one active group of hydroxyl, carbonyl and amino groups on the surface of the film material by a modification process, and these active groups can increase the composite strength of the film material and the metal film layer. Figure 4 As shown, in one embodiment, a plurality of hydroxyl groups (—OH) are introduced on the surface of the film material 100 through a modification process.

[0046] The present application is further described below in conjunction with specific embodiments.

[0047] Example 1: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, perform a calendering operation on the film material so that the thickness of the film material is 5 μm and the surface roughness is 0.012 μm, and perform a stretching operation on the film material so that the D90 pore size of the embedded structure of the film material is 0.2 μm. A copper film layer with a thickness of 0.5 μm is formed on the film material by a magnetron sputtering deposition process.

[0048] Example 2: Take PE powder with a D50 particle size of 10 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5 μm, the D90 pore size of the embedded structure is 0.8 μm, and the surface roughness is 0.1 μm. A copper film layer with a thickness of 0.5 μm is formed on the film material by a magnetron sputtering deposition process.

[0049] Example 3: Take PE powder with a D50 particle size of 5 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5 μm, the D90 pore size of the embedded structure is 0.5 μm, and the surface roughness is 0.05 μm. A copper film layer with a thickness of 0.5 μm is formed on the film material by a magnetron sputtering deposition process.

[0050] Example 4: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5 μm, the D90 pore size of the embedded structure is 0.2 μm, and the surface roughness is 0.012 μm. A copper film layer with a thickness of 2 μm is formed on the film material by a magnetron sputtering deposition process.

[0051] Example 5: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5 μm, the D90 pore size of the embedded structure is 0.2 μm, and the surface roughness is 0.012 μm. A copper film layer with a thickness of 1.2 μm is formed on the film material by a magnetron sputtering deposition process.

[0052] Example 6: Take PE powder with a D50 particle size of 5 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5 μm, the D90 pore size of the embedded structure is 0.5 μm, and the surface roughness is 0.05 μm. A copper film layer with a thickness of 1.2 μm is formed on the film material by a magnetron sputtering deposition process.

[0053] Example 7: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. Separate the film material from the fluorocarbon film, and form a copper film layer with a thickness of 1.2 μm on the film material by a magnetron sputtering deposition process.

[0054] Example 8: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a fluorocarbon film. Heat the PE powder by infrared laser irradiation to make the PE powder fuse to form a film material. Introduce hydroxyl groups on the surface of the film material by chemical vapor deposition, separate the film material from the fluorocarbon film, and form a copper film layer with a thickness of 1.2 μm on the film material by a magnetron sputtering deposition process.

[0055] Example 9: Take PE powder with a D50 particle size of 2 μm as a polymer powder, and lay the PE powder on a 1.2 μm thick copper foil layer. Heat the PE powder by infrared laser irradiation to make the PE powder melt to form a film material. A copper film layer with a thickness of 1.2 μm is formed on the side of the film material away from the copper foil layer by a magnetron sputtering deposition process.

[0056] Comparative Example 1: Take PE powder with a D50 particle size of 2μm as the polymer powder and place it in an extruder, and extrude the molten PE powder into a mold through the extruder to form a film material, and perform calendering and stretching operations on the film material so that the thickness of the film material is 5μm and the surface roughness is 1.5nm, and a copper film layer with a thickness of 0.5μm is formed on the smooth film material through a magnetron sputtering deposition process.

[0057] Comparative Example 2: PE powder with a D50 particle size of 2 μm is taken as a polymer powder and placed in a casting machine to prepare a film material. The film material is calendered and stretched so that the film material has a thickness of 5 μm and a surface roughness of 1 nm. A copper film layer with a thickness of 0.5 μm is formed on the smooth film material through a magnetron sputtering deposition process.

[0058] The composite current collectors prepared in the above embodiments were subjected to peeling force test: Take a test sample with a size of 15mm×100mm and pre-treat it under standard laboratory conditions (23±2°C, relative humidity 50±5%) for at least 24 hours before testing. Use a tensile testing machine that complies with ISO 7500-1 standard and a 2kg standard rubber roller.

[0059] Test steps: Attach the test tape evenly to a clean stainless steel plate, and evenly attach the test samples of each embodiment and comparative example to the tape to ensure that there are no bubbles. Use a 2kg standard roller to squeeze back and forth twice, then attach the test tape to the sample surface again, and then use the above roller to squeeze twice. Fix the test sample on a tensile machine, and stretch the tape and the test sample at 180°, and perform a peel test at a speed of 100mm / min.

[0060] The test results of the peel force test are shown in Tables 1 and 2 below: Table 1 - Peel force test results Experimental Group Peel force (N / m) Example 1 16.25 Example 2 16.17 Example 3 17.11 Example 4 16.38 Example 5 16.51 Example 6 17.81 Example 7 15.89 Example 8 17.60 Comparative Example 1 13.68 Comparative Example 2 13.86 Table 2 - Peel test results of Example 9 Experimental Group Peeling force between copper foil and film (N / m) Peeling force between copper film layer and film material (N / m) Example 9 15.08 15.83 It can be seen from Table 1 and Table 2 above that, compared with the comparative examples, the peeling force between the copper film layer and the film material of each embodiment is greater, that is, the composite strength is higher, making the copper film layer less likely to be peeled off from the film material. Comparing Examples 1 to 3, it can be seen that compared with Examples 1 and 2, Example 3 has a higher peeling force between the film material and the copper film layer. Specifically, the embedded structure and surface roughness of Example 3 are at a better value, so that the copper atoms of the copper film layer are better embedded in the embedded structure, increasing the mechanical interlocking effect between the copper film layer and the film material, thereby increasing the composite strength of the copper film layer and the film material. Comparing Example 1, Example 4 and Example 5, it can be seen that compared with Examples 1 and 4, Example 5 has a higher peeling force between the film material and the copper film layer. This is because the copper film layer of Example 5 is at a more suitable thickness, which avoids the situation of discontinuity or surface peeling of the copper film layer, so that the copper film layer and the film material have better composite strength. Comparing Examples 1-6, it can be seen that the PE powder particle size, embedded structure pore size, surface roughness and copper film layer of Example 6 are selected at the same time. The film material and copper film layer of Example 6 have the best peeling resistance in each embodiment. Comparing Example 7 and each comparative example, it can be seen that Example 7 is welded by PE powder so that the surface of the film material has an embedded structure. Although calendering and stretching are not performed to control the pore size of the embedded structure and the surface roughness of the film material, the peeling force can still be increased, so that the film material and the copper film layer have a better composite strength. Comparing Examples 7 and 8, it can be seen that by introducing hydroxyl groups on the surface of the film material, the peeling force between the film material and the copper film layer can be significantly increased, so that the film material and the copper film layer have a better composite strength. This is because after the introduction of hydroxyl groups on the surface of the film material, it can provide a reaction site when copper atoms begin to be deposited, which is conducive to the uniform growth of the copper film layer, and a more uniform and dense copper film layer deposition is achieved, and it is conducive to the formation of a stronger chemical bond between the copper atoms and the surface of the film material, and the copper film layer and the film material are combined to achieve a stronger composite strength. By comparing Example 9 and the comparative examples, it can be seen that, when the copper foil layer is used as the preset workpiece, the film material can still have a large peeling force with the copper film layer and the copper foil layer, thereby achieving better compounding of the film material with the copper film layer and the copper foil layer.

[0061] The ternary material NCM is selected as the positive electrode active material. The positive electrode active material NCM, the conductive agent carbon black, and the binder PVDF are mixed in N-methylpyrrolidone solvent to prepare a positive electrode slurry. The prepared positive electrode slurry is then coated on the composite current collector of each embodiment and comparative example, and dried to obtain a positive electrode sheet.

[0062] Graphite is selected as the negative electrode material, and it is mixed with a binder and a conductive agent in an ethylene glycol solvent to prepare a negative electrode slurry; the negative electrode slurry is then coated on a composite current collector, and then dried in a vacuum drying oven at 120° C. to obtain a negative electrode sheet.

[0063] PVDF is selected as the diaphragm; the electrolyte is a mixture of ethyl methyl carbonate, dimethyl carbonate and ethylene carbonate in a ratio of 1:1:1, and the solute of the electrolyte is 1 mol / L lithium hexafluorophosphate.

[0064] The positive electrode sheet, negative electrode sheet, separator and lithium ion electrolyte are assembled into a lithium ion battery.

[0065] Take the lithium ion batteries of the above embodiments and comparative examples for cycle life test: Use a battery charge and discharge tester to test the battery at 25°C for charge and discharge cycle. The charge and discharge system is: charge to 4.25V at 0.5C constant current, then charge at constant voltage until the current drops to 0.02C, and after standing for 5 minutes, discharge the battery to 2.5V at 0.5C constant current. This is one cycle. The number of cycles of the battery charge and discharge tester is set to 5000 times. As the battery cycles, the battery capacity continues to decay. When the capacity decays to the first discharge capacity Q 放 The number of cycles experienced when the battery reaches 80% of its rated capacity is recorded as the cycle life of the battery.

[0066] The test results of the cycle life test are shown in Table 3 below: Table 3 - Test results of cycle life test Experimental Group Cycle life (times, 25°C, 1C / 1C, capacity retention rate 80%) Example 1 1076 Example 2 1130 Example 3 1195 Example 4 1119 Example 5 1162 Example 6 1278 Example 7 1032 Example 8 1260 Example 9 930 Comparative Example 1 628 Comparative Example 2 614 It can be seen from Table 3 above that compared with the lithium-ion battery prepared in the comparative example, the cycle life of the lithium-ion battery of each embodiment is longer, that is, the lithium-ion battery of each embodiment has a better service life. This is because the composite strength between the copper film layer and the film material of the composite current collector of each embodiment is higher, so that the composite current collector of each embodiment has better mechanical strength. In this way, during the long-term use of the lithium battery, the copper film layer is not easy to peel off, so that the lithium-ion battery can have a longer service life. In each embodiment, the better the composite current collector performs in the peeling force test, the better the cycle life is after being prepared as a lithium battery. This is because when the composite strength between the copper film layer and the film material is better, the film material and the positive electrode active material can be prevented from peeling off, so that the positive electrode active material can play a role more lastingly, thereby making the cycle performance better.

[0067] Then take the film material of Example 1 and observe it under a microscope. Figure 5 As shown, it can be seen that the surface of the film material is granular, and the embedded structure formed between these particles is conducive to the embedding of metal atoms, thereby increasing the composite strength of the film material and the metal film layer.

[0068] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a composite current collector, characterized in that: The steps include: Laying polymer powder on the preset workpiece; Heating the polymer powder so that the polymer powder is melted to form a film material; A metal film layer is formed on the film material through a deposition process.

2. The method for preparing a composite current collector according to claim 1, characterized in that: After the step of heating the polymer powder so that the polymer powder is welded to form a film material, the step further includes: The film material is separated from a preset workpiece.

3. The method for preparing the composite current collector according to claim 1, characterized in that: After the step of separating the film material from the preset workpiece, the following steps are further included: The film material is subjected to calendering and / or stretching operations.

4. The method for preparing a composite current collector according to claim 2, characterized in that: The preset workpiece includes a release material.

5. The method for preparing a composite current collector according to claim 1, characterized in that: The predetermined workpiece includes a metal foil layer.

6. The method for preparing a composite current collector according to claim 1, characterized in that: Before the step of forming a metal film layer on the film material by a deposition process, the step further includes: At least one active group among hydroxyl, carbonyl and amino is introduced into the surface of the film material through a modification process.

7. The method for preparing a composite current collector according to claim 1, characterized in that: The thickness of the metal film layer is 0.5-2 μm.

8. The method for preparing a composite current collector according to claim 1, characterized in that: The D50 particle size of the polymer powder is 2-10 μm, and / or an embedded structure is formed on the surface of the membrane material, and the pore size of the embedded structure is 0.2 μm-0.8 μm.

9. The method for preparing a composite current collector according to claim 1, characterized in that: The surface roughness of the membrane material is 0.012-0.1 μm.

10. A composite current collector, characterized in that: The composite current collector is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Composite metal foil, preparation method therefor and use thereof

    WO2026143797A1